PENGARUH DOSIS PUPUK UREA TERHADAP PERTUMBUHAN RUMPUT MOMBASA (Panicum maximum var. Mombasa): EFFECT Of UREA FERTILIZER DOSAGE ON THE GROWTH OF MOMBASA GRASS (Panicum maximum var. Mombasa) (Universitas Djuanda Bogor, 2023)
This study aims to determine the effect of urea fertilizer on the growth of Mombasa (Panicum maximum var. Mombasa). This research was conducted in the Greenhouse of the Livestock and Forage Cultivation Laboratory, Faculty of Animal Husbandry, Jambi University. The experiment used in this study was Completely Randomized (CRD) with 5 designs and 5 replications. The treatments used in this study were P0 = 0 grams/polybag, P1 = 4.45 grams/polybag, P2 = 8.90 grams/polybag, P3 = 13.36 grams/polybag, P4 = 17.81 grams/polybag. Observed data in this study were root dry weight, number of tillers, plant height, leaf length, leaf width, leaf area and biomass dry weight. The data obtained were analyzed using analysis of variance (ANOVA). All data that have a significant effect will be followed by a significant difference test (Duncan). The results of the analysis showed that the treatment of urea fertilizer with different doses gave no significant effect (P<0.05) on the number of tillers, leaf area and root dry weight. However, it had a significant effect (P>0.05) on leaf length, leaf width, plant height increase, average plant height increased and biomass dry weight. From the results of the research that has been carried out, it can be found that urea fertilizer treatment with dosage of 13.36 g gave the best effect than other treatments, especially on leaf width, leaf area, canopy dry weight, plant height increase and average height gain, for treatment 17 ,81 g gave the best effect among other treatments, namely on leaf length